THE INFLUENCE OF SILICA CALCINATION TEMPERATURE VARIATION TO THE HYDROPHOBICITY AND TRANSMITTANCE ON GLASS SUBSTRATE - Rohmah, Roihatur; Zainuri, Mochamad (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2020)
The hydrophobic surface can be self-cleaning. The hierarchy of surface roughness affects the hydrophobic surface. In this research, the hydrophobic surface was fabricated by modification of surface roughness from the composite filler. Natural silica was used as a filler and was done a variation of calcination temperature to modify the hierarchy of roughness formed. The variation of calcination temperature was 800°C, 1000°C, 1200°C, and 1400°C. The coating method was a dip-coating method by 30-second long immersion. A glass as coating media was coated by PVDF/SiO2 composite. The hydrophobic surface could be known from the value of the water contact angle (WCA) formed. If a water contact angle more than 90°, the surface could be called the hydrophobic surface. In this research, the hydrophobicity aspect cause of variation of calcination temperature was known from the value of water contact angle formed on the surface of PVDF/SiO2 composite coating 800°C, 1000°C, 1200°C, and 1400°C was 117,12° ± 0,98°, 107,80° ± 0,91°, 121,31° ± 1,45°, and 111,75° ± 1,47°, respectively.